Magneto‐Optical Bi:YIG Films with High Figure of Merit for Nonreciprocal Photonics. Issue 13 (23rd April 2019) - Fakhrul, Takian; Tazlaru, Stana; Beran, Lukáš; Zhang, Yan; Veis, Martin; Ross, Caroline A.
Abstract: Thin film magneto‐optical (MO) materials are enablers for integrated nonreciprocal photonic devices such as isolators and circulators. Films of polycrystalline bismuth‐substituted yttrium iron garnet (Bi:YIG) have been grown on silicon substrates and waveguide devices, in which an yttrium iron garnet (YIG) seedlayer is placed either above or below the active Bi:YIG layer to promote crystallization. The films exhibit a high MO figure of merit of up to 769° dB −1 at 1550 nm wavelength. Growth of single phase Bi:YIG on the sidewalls of waveguides is demonstrated, which can be used in nonreciprocal transverse electric (TE)‐mode devices. Abstract : This work presents developments in the integration of magneto‐optical materials into photonic circuits. Successful demonstration of top‐down crystallized bismuth‐substituted yttrium iron garnet films on silicon is shown, leading to figures of merit at 1550 nm above one order of magnitude higher than previously reported values for polycrystalline garnets. Sidewall growth of garnets, essential for transverse electric‐mode isolators, is also demonstrated.